2017
DOI: 10.1186/s13046-017-0641-y
|View full text |Cite
|
Sign up to set email alerts
|

Adipocytes promote cholangiocarcinoma metastasis through fatty acid binding protein 4

Abstract: BackgroundThe early occurrence regional nodal and distant metastases cholangiocarcinoma (CCA) is one of the major reasons for its poor prognosis. However, the related mechanisms are largely elusive. Recently, increasing evidences indicate that adipocytes might be involved in the proliferation, homing, migration and invasion of several malignancies. In the present study, we attempt to determine the effects and possible mechanisms of adipocytes on regulating progression of CCA.MethodsAdipocyte–CCA cell co-cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 64 publications
0
21
0
Order By: Relevance
“…content of saturated versus unsaturated fatty acids) is intimately tied to protein dynamics and membrane fluidity. In particular, monounsaturated fatty acids, derived from saturated fatty acids by the action of SCDs, have been associated with the acquisition of malignant features [51, 52]. However, how lipid metabolism is concatenated with CSC fate remains un understudied domain of stem cell biology [53].…”
Section: Discussionmentioning
confidence: 99%
“…content of saturated versus unsaturated fatty acids) is intimately tied to protein dynamics and membrane fluidity. In particular, monounsaturated fatty acids, derived from saturated fatty acids by the action of SCDs, have been associated with the acquisition of malignant features [51, 52]. However, how lipid metabolism is concatenated with CSC fate remains un understudied domain of stem cell biology [53].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that adipocytes contribute to EMT, invasion, proliferation and progression, in several cancer types [83][84][85][86][87]. Nie et al, [88] found that co-culture with adipocytes led CCA cells to express mesenchymal biomarkers overexpression and cell-to-cell adhesion alteration. The acquisition of these mesenchymal markers in CCA cells could be due to adypocite-derived FAs.…”
Section: Lipid Metabolism In Ccamentioning
confidence: 99%
“…The acquisition of these mesenchymal markers in CCA cells could be due to adypocite-derived FAs. In fact, they showed that the adipocyte-derived FABP4 mediated migration, invasion and lipid accumulation in CCA, by shifting FAs between adipocytes and cancer cells [88].…”
Section: Lipid Metabolism In Ccamentioning
confidence: 99%
“…Kshipra et al (48) observed that overexpression of FABP4 plays a key role in aggressive metastasis of ovarian cancer via various metabolites and protein pathways. Likewise, FABP4 has crucial effects on adipocyte-induced cholangiocarcinoma metastasis (49). Collectively, metabolic disorder is among the leading causes of tumour development.…”
Section: Discussionmentioning
confidence: 99%